A Statewide Analysis of EMS' Pediatric Transport Destination Decisions. (2nd September 2020) - McManus, Kayla; Finlay, Erik; Palmer, Sam; Anders, Jennifer F.; Hendry, Phyllis; Fishe, Jennifer N.
Abstract: Introduction: Deciding where to transport a patient is a key decision made by emergency medical services (EMS), particularly for children because pediatric hospital resources are regionalized. Since evidence-based guidelines for pediatric transport destinations are being developed, the purpose of this study was to use a large statewide EMS database to describe current patterns of EMS providers' transport destination decisions for pediatric patients. Methods: This is a retrospective study of pediatric transports from 2011-2016 in EMS Tracking and Reporting System (EMSTARS), Florida's statewide EMS database. We included patients greater than 1 day and less than or equal to 18 years who were primary EMS scene transports. Our primary outcome variable was 'reason for choosing destination.' We performed descriptive and comparative analysis between closest facility and all other 'reason for choosing destination' choices. We used geospatial analysis to examine destination choice in urban and rural counties. Results: Our final study sample was 446, 274, and 48.2% of patients had closest facility as their 'reason for choosing destination.' The next largest category was patient/family choice (154, 035 patients, 35.7%). Closest facility patients were older (median age 12 versus 10 years, p < 0.0001) and had shorter median EMS transport times (11.3 versus 15 minutes, p < 0.0001) compared to all other destination decisions. Notably, 60% of respiratory distress patients' and 44% of seizure patients' reason for choosing destination was something other than closest facility. Geospatial analysis revealed that fewer rural patients were documented as closest facility compared to urban (43.9% versus 47%, p < 0.0001). Correspondingly, more rural patients' destination decision was patient/family choice than urban patients (36.3% versus 34.3%, p < 0.0001). Conclusions: This large, statewide study describes EMS' reason for choosing destination for pediatric patients. We found that just under half of patients were documented as closest facility, and over one-third as patient/family choice. Significant differences in destination reasons were noted for rural versus urban counties. This study can help those currently developing pediatric EMS destination guidelines by revealing a high proportion of patient/family choice and identifying conditions with high proportions of destination reasons other than closest facility.